Modern Insulin, Device, and Technology: Tips For Clinicians - Hasan, ABM Kamrul (Bangladesh Journal of Medicine, 2023)
Insulin has been a lifesaving treatment for people with diabetes since its discovery in 1921. However, the way insulin is delivered evolved over time. Modern insulin, devices, and technology have transformed the management of diabetes and improved the quality of life for millions of people worldwide.Modern insulins are designed to match the needs of people with diabetes better. Traditional insulins, such as regular and NPH insulin, have a delayed onset and peak, making it difficult to manage blood sugar levels. Newer insulins, such as rapid-acting insulin analogs like aspart, glulisine, and lispro, have a faster onset and shorter duration of action, allowing for greater dosing and timing flexibility. Long-acting insulin analogs, like glargine and detemir, provide more consistent blood sugar control and less hypoglycemia risk.Insulin delivery devices have also advanced significantly. The most common device is the insulin pen, which looks like a large pen and uses disposable insulin cartridges. The pen has replaced traditional syringes and vials for many people with diabetes, offering greater convenience and ease of use. Insulin pumps are also becoming more popular, especially among people with type 1 diabetes. A pump delivers insulin through a catheter inserted under the skin, which can be programmed to provide a continuous infusion of insulin or a bolus dose before meals.Technological advancements have also revolutionized diabetes management. Continuous glucose monitoring (CGM) systems use a small sensor inserted under the skin to measure glucose levels every few minutes, providing real-time data to help people make more informed decisions about insulin dosing and food choices. Some CGM systems also offer alerts for high and low blood sugar levels, making it easier to avoid dangerous fluctuations. Automated insulin delivery systems, also known as closed-loop systems or artificial pancreas systems, use CGM data to automatically adjust insulin delivery, reducing the burden of constant monitoring and decision-making for people with diabetes.In summary, modern insulin, devices, and technology have greatly improved the management of diabetes, allowing for better blood sugar control and a better quality of life for people with diabetes. As technology continues to advance, the future of diabetes management looks promising. Bangladesh J Medicine 2023; Vol. 34, No. 2(1) Supplement: 191